Spondylocostal dysplasia – Jarcho–Levin syndrome: A case report - Chandra Babu, Aruna; Ameena Bashir, Rani; Vayal Thrikkovil, Sakeer; Vinod, Neena (Indian Journal of Case Reports, 2024)
Jarcho–Levin syndrome (JLS) refers to a rare congenital disorder, inherited in an autosomal recessive pattern, which presents as a spectrum of clinical and radiographic abnormalities of the spine and chest. The precise genetic basis of JLS is not clear, hence diagnosis is usually made by typical clinical features such as malformed ribs which are malaligned, crowded, fused, and bifid with a posterior symmetric fusion of all the ribs at the costovertebral joints and flared anteriorly giving “crab-like” or “fan-like” appearance to the chest. Here, we report the case of a baby boy who presented with respiratory distress and was noted to have the characteristic skeletal abnormalities, which include congenital scoliosis with vertebral anomalies, multiple fused ribs with congenital heart disease large 7-mm apical ventricular septal defect (VSD), multiple mid-muscular VSD with increased pulmonary blood flow, 5 mm ostium secundum atrium septal defect, and left ventricular (LV) dilatation with LV failure. The diagnosis of JLS is made if there is a characteristic physical appearance with radiological findings in the clinical setting of thoracic insufficiency. In this case report, we intend to bring forth the learning point that, when a baby is presented with respiratory distress and vertebral, as well as, thoracic cage malformations, the diagnosis of JLS should be kept in mind, if left untreated there is a chance of respiratory failure and thereby making it potentially fatal.